All-optical router at single-photon level by interference. (12th October 2015) - Yan, Wei-Bin; Liu, Bao; Zhou, Ling; Fan, Heng
Abstract: The realization of the all-optical router with multiple input ports and output ports will have direct application to achieve the quantum network. We present a scheme of all-optical routing of coherent-state photons in a waveguide-cavity coupled system. Our router has four input ports and four output ports. The routing of photons is based on the interference. The outcomes show that the transport of the coherent-state photons injected through any input port can be controlled by the phases of the coherent-state photons injected through other input ports. This control can be realized at the single-photon level and requires no additional control fields. Therefore, the all-optical routing at single-photon level can be achieved.